Alokasi Dana Desa dalam Pengentasan Kemiskinan di Pulau Sumatera - Anis Marsela (Inspirasi Nusantara, 2021)
Village fund allocation is a source of funds aimed at villages, originating from APBN funds which are actualized through district or city APBD funds, where these funds are for the development and empowerment of village communities. The allocation of village funds is primarily used to alleviate poverty and inequality that occurs in the community. The purpose of this study was to determine the effect of village fund allocations in alleviating poverty in Sumatra Island. This study uses a descriptive method with a quantitative approach using time series data, 2015-2017, from many villages from 10 provinces on the island of Sumatra. The data analysis technique used in this research is simple linear regression analysis. The results of this study reveal that there is a significant negative effect of the allocation of village funds on poverty in Sumatra Island, so it can be concluded that the allocation of village funds can alleviate poverty following its objectives.